Early determinants of lung function in African infants - Gray, Diane Margaret (Division of Pulmonology, 2016)
Childhood respiratory disease remains a major contributor of morbidity and mortality globally and both paediatric and adult chronic respiratory illness is increasing in prevalence worldwide. This burden of respiratory disease is heaviest in low-middle income countries (LMIC), areas that have a high prevalence of known risk factors for respiratory disease, such us overcrowding, poverty and environmental air pollution. Much chronic respiratory illness has its origin in early life; further low lung function in infancy is associated with later respiratory illness. However, there is limited data on lung function in African infants despite a high prevalence of respiratory disease. Understanding the determinants of infant lung function will improve our understanding of prevention and management of respiratory disease. This thesis aimed to describe lung function in South African infants from six weeks to one year and to investigate the impact of prenatal and early environmental exposures on lung function in infancy. Infants enrolled in the Drakenstein Child Health Study, a multidisciplinary birth cohort study investigating the aetiology and outcome of early life lower respiratory tract infections (LRTI), were included. Seven hundred and forty one infants were enrolled from June 2012 to February 2015. Infants had lung function measured at six (4-10) weeks of age and one year (11-14 months). Measurements, made with the infant breathing via a facemask during natural sleep, included tidal breathing, exhaled nitric oxide, sulphur hexafluoride multiple breath washout and the forced oscillation technique. Information on antenatal exposures was collected using questionnaires and urine cotinine. Household benzene was measured antenatally. The chapters of the thesis are presented as published manuscripts that describe the establishment of infant lung function for the first time in South Africa and the development of normative lung function in the first year of life. The final chapters investigate the impact of early life exposures, most notably LRTI, on lung function at six weeks and one year. The thesis concludes that infant lung function testing is feasible in a community setting in 11 a LMIC like South Africa. Size, gender and ethnicity are important determinants of lung function. Lung function of South African infants is not well predicted by European reference equations, highlighting the importance of using population specific reference data when interpreting lung function tests. The study identifies several factors including maternal smoking, maternal alcohol and household benzene exposure during pregnancy, associated with altered early lung function. In addition tracking of lung function in the first year of life is described in this cohort of African infants living in a high respiratory disease burden setting. The study identifies risk factors for impaired lung function at one year independent of low baseline lung function: LRTI, household smoke exposure and infant nutrition, factors amenable to public health intervention. Given the fact that infant lung function tracks into later life and plays a role in chronic respiratory disease, preventing respiratory illness in young children, reducing exposure to environmental tobacco and maximising nutrition are key priorities in the strengthening of child respiratory health. Long-term study of lung function and respiratory disease in these infants is a priority in order to develop new strategies to strengthen child health.